A critical review on factors affecting the two-stage anaerobic digestion of biodegradable solid waste - Pham, Van Dinh; Leu Tho, Bach; Pham, Van Toi; Do, Van Manh; Tran Thanh, Liem (Vietnam Journal of Science and Technology, 2025)
Anaerobic digestion (AD) technology has attracted considerable attention from the scientific community and has become a crucial component of sustainable solid waste management systems. It is the only biotechnological process capable of converting high-moisture biomass waste into energy through a series of biochemical steps, including hydrolysis, acidogenesis, acetate production, and methane generation. Notably, the two-stage anaerobic digestion (TAD) process, which separates methanogenesis and hydrolysis into two distinct reactors, offers significant advantages over conventional methods. The performance of AD systems is influenced by various factors, including growth conditions (such as carbon-to-nitrogen ratio, pH, and temperature), operational parameters (such as retention time and organic loading rate), feedstock pretreatment, and potential inhibitors. While these aspects have been widely studied in single-stage anaerobic digestion systems, research on their impact in TAD systems remains limited. This study aims to provide a comprehensive review of the factors affecting TAD systems. It synthesizes the latest research findings from recent years and discusses optimal operating conditions to enhance TAD performance.